The Relationship Of Logotherapy In Improving The Self-Concept Of The Elderly In The Trisna Werda Social Home Budi Mulia II Cengkareng - Tri Setyaningsih; Yurita Mailintina; Ribka Sabarina Panjaitan; Dian Fitria; Ary Rahmaningsih (Sean Institute, 2024)
Old age is a time when everyone hopes to live a calm, peaceful and happy life and enjoy a retirement period with their children and grandchildren by pouring out love. However, in reality, not all elderly people can get a chance at life and get the ideal living conditions as desired. The purpose of this study is to determine the relationship between logotherapy in improving the self-concept of the elderly in the Trisna Werda Budi Mulia II Cengkareng social institution. This type of research is quantitative with a Cross-Sectional design. The research approach used is a quantitative approach, namely the use of questionnaires and survey research techniques which are components of quantitative research. This study evaluates the effectiveness of logotherapy in improving the self-concept of the elderly in the Trisna Werda Budi Mulia II Cengkareng Social Home. The results of the analysis showed that there was a positive and significant relationship between logotherapy and the improvement of self-concept of the elderly, with a Pearson correlation of 0.672 and a significance value of 0.000. In conclusion, logotherapy is effective in improving the self-concept of the elderly and their psychological well-being, providing significant benefits in meaning life and improving their quality of life.